Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Yang Terdaftar Pada Bursa Efek Indonesia - Wendy Clarissa Santoso, Elizabeth Sugiarto Dermawan (Jurnal Paradigma Akuntansi, 2021)
This research aims to obtain empirical evidence about liquidity, firm growth, capital structure, profitability, and company age on firm value of manufacturing companies on the Indonesian Stock Exchange (IDX) during 2017-2019. Samples taken in this study as many as 232 data based on non probability sampling methods and purposive sampling techniques. This study uses multiple regression analysis and helped by SPSS program version 21 and Microsoft Excel 2013. The results of this research showed that firm growth and profitability had a significant positive effect on firm value. Liquidity and capital structure had a significant negative effect on firm value. Company age had a negative effect but do not have a significant effect on firm value. The implication of this research is the need to increase the determinants of firm as an investor’s consideration in doing investment.